Adult Literacy, Heterogeneity and Returns to Schooling in Chile - Patrinos, Harry Anthony; Sakellariou, Chris (Taylor and Francis, 2013)
We examine the importance of adult functional literacy skills for individuals using a quantile regression methodology. The inclusion of the direct measure of basic skills reduces the return to schooling by 27 percent, equivalent to two additional years of schooling, while a one standard deviation increase in the score increases earnings by 20 percent. For those who are less skilled, more education contributes little to earnings; rather skills are the key to higher earnings. The non-schooling component of skill is a significant contributor to earnings, but not the component associated with years of schooling.